Characteristics of uranium recovery from phosphoric acid by an aminophosphonic resin and application to wet process phosphoric acid - Cheira, Mohamed Farid (European Journal of Chemistry, 2015)
The chelating aminomethylphosphonic resin Amberlite IRC747 is used for uranium recovery from a synthetic phosphoric acid solution. The operating conditions of uranium extraction have been experimentally optimized by the batch technique viz., the phosphoric acid concentration, the contact time, the initial uranium concentration and the temperature. The effect of some interfering ions upon the effective capacity of the resin has also been examined. It has thus been found that the maximum uranium adsorption capacity of the studied chelating resin was found to attain 86.5 mg/g at 5 M phosphoric acid using 0.1 g resin for 120 min contact time with 50 mL acid assaying 200 mg U/L and room temperature. The obtained equilibrium data agreed well with the Langmuir isotherm model and the relevant thermodynamic parameters (ΔG, ΔH and ΔS) were evaluated and the uranium adsorption was found to be an endothermic reaction and of spontaneous nature. From the kinetic experiments it was shown that U(VI) adsorption followed the pseudo-second order kinetics model and the intraparticle diffusion model. Also, it has been possible to reveal from the kinetic and isotherm data the chemisorption nature of uranium on the Amberlite IRC747 resin. The adsorbed uranium ions can almost be completely eluted with 0.8 M (NH4)2CO3 solution from the loaded resin at room temperature. The studied optimized conditions have successfully been applied for uranium recovery from Abu Zaabal wet process phosphoric acid (WPPA).